A Critique of the International Legal Regime Applicable to Terrorism (Strathmore Law Journal, 2016)
Terrorism is a global phenomenon that permeates state borders and predominantly causes immeasurable suffering to civilians. The need for international cooperation and concerted efforts in combating terrorism cannot be gainsaid. Already, sectoral instruments have been passed to regulate certain aspects of terrorism. However, without a single terrorism specific instrument, acts of terrorism generally classified will fall under spheres of international law which include; public international law, international criminal law, international humanitarian law, human rights and refugee law. This paper makes a critical analysis of these spheres of international law and how they apply to states’ counter-terrorism efforts.